2015
DOI: 10.17795/semj27392
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Serum Zinc Level Between Neonates With Jaundice and Healthy Neonates

Abstract: Background: Neonatal jaundice is the most common cause of hospitalization in the first month of life. Factors that reportedly affect the severity of neonatal jaundice include: maternal, prenatal and neonatal factors as well as environmental factors (such as zinc). Animal study demonstrated a decrease in serum bilirubin level after zinc treatment in hyperbilirubinemic rats. Objectives: The current study aimed to investigate serum zinc level in the neonates with idiopatic jaundice. Patients and Methods: A case-c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
10
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 12 publications
8
10
0
Order By: Relevance
“…Some studies showed that higher levels of Zn had protective effects against hyperbilirubinemia and this in agreement with our results that Zn supplementation was associated with decreased in serum bilirubin [16].…”
Section: Discussionsupporting
confidence: 93%
“…Some studies showed that higher levels of Zn had protective effects against hyperbilirubinemia and this in agreement with our results that Zn supplementation was associated with decreased in serum bilirubin [16].…”
Section: Discussionsupporting
confidence: 93%
“…[13] With respect to demographic data of studied groups, the percentage of males was 56 percent higher than 44 percent of females, the male to female ratio in cases was 1.2:1. This in agreement with Boskabadi et al [3] who reported that male to female ratio was (1.2:1) and Hasan [4] who reported that male to female ratio was (1.3:1) with male predominance. In fact, male newborns are always more susceptible to neonatal jaundice, although the cause remains unknown.…”
Section: Discussionsupporting
confidence: 92%
“…In fact, male newborns are always more susceptible to neonatal jaundice, although the cause remains unknown. [14] The control mean age was 6.371.75 days that was comparable to the study of Boskabadi et al [3] who showed that the mean age 6.75 ± 4.88 days in the control group. In addition, the mean gestational age in cases was 38.15 ± 1.19 week and in control group was 38.13± 1.11 week that was comparable to the study of Tan et al [15] who reported GA of 38.48±1.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…16 The present study confirmed the findings of other recent studies that have reported the reduction of serum Zn level in icteric infants, when the serum bilirubin increased more likely due to competitive effect. 17,18 In this study the mean serum Zn level in newborns at admission (before EXT) was 48.53±4.94 μg/dl that was at a level lower than normal range in healthy newborns (50-100 μg/dl).…”
Section: Discussionmentioning
confidence: 50%